Numerical study of the effect of martensite plasticity on the forming limits of a dual-phase steel sheet - Schwindt, Claudio Daniel (2016)
The formability prediction of dual-phase steel sheets is highly important in the present automotive industry. In this study, the forming-limit curve (FLC) of a DP-780 steel sheet is predicted based on the well-known Marciniak and Kuczynski (MK) theory using a Visco-Plastic Self-Consistent (VPSC) crystal-plasticity scheme. To calibrate the polycrystal model, the stress–strain curves of the ferritic and martensitic phases are inferred by accounting for three martensitic plastic behaviors. Thus, the effect of martensitic plasticity on the FLC simulation can be analyzed. In addition, two different hardening laws – namely saturation and Voce models – are considered in order to study the effects of the extrapolated hardening behavior on the shape of the predicted FLCs. The best agreement with experimentation is found when the FLCs are calculated using the saturation hardening law and when the martensite deformation is either not allowed or retarded to occur after the point of necking. An analysis of the ferritic/martensitic slip system activity inside and outside the MK instability band suggests that, within the MK-VPSC framework, localization occurs much faster in the ferritic than in the martensitic phase. In addition, it is found that, unlike uniaxial tension, after plane-strain deformation and equi-biaxial stretching there is a strong correlation between the orientation of the ferritic grain and the strain that it accommodates. The predictive capability of the model is also confirmed by comparing the measured and simulated crystallographic textures close to necking.